Reingeniería de procesos en el Taller de hojalatería e industrial San José de la ciudad de Loja, Cantón Loja - Hidalgo Jiménez, Jhinson Ramiro (2017)
Currently the reengineering of processes, is a major factor for success of an enterprise, involving significant improvements to their management activities and operation; Likewise involves to examine step by step them processes to develop is from its beginning until the delivery of the product to the consumer end; by aims that this investigative work "process REENGINEERING IN THE body REPAIR WORKSHOP and INDUSTRIAL SAN JOSE, FROM THE CITY OF LOJA, PROVINCIA OF LOJA", posing as a general objective the realization of a re-engineering of processes in the body repair workshop and Industrial San Jose, from the city of Loja, Loja Canton. For to make the present work research is used some methods as deductive-inductive, analytic, descriptico, synthetic, statistical; technical as the observation direct, research bibliographic, interview applied to the Manager of the workshop of Tin San José and the survey carried out to them employees and customers of the entity. To the make the diagnosis situational of the workshop is could identify that presented problems such as: not have with a chart, not have a mission, vision, not is have made some analysis of the functions and processes that is carry to out in the workshop. Also is could identify processes strategic and operating that is carried to out to make the product; without consider times, responsible for or the waste of the material to deal with it. Within those processes strategic are them of acquisition, where in your home is took a time of 360 minutes, while with the reengineering is used 330 minutes; Likewise have the process of sale both in the sector private as public, in the first case is considered a time estimate of 175 minutes, but with the reengineering is takes 165 minutes; as for the second case in first instance it took a time of 3870 minutes; so with the re-engineering was reduced to 2480 minutes. In the case of billing the current process is carried out in 110 minutes and with re-engineering would be in a time of 100 minutes. So also have the processes operating as are the process of production where is leads to out in a time of 1320 minutes, by what with the reengineering is takes 835 minutes; While in the process of placement of the channel currently is used 705 minutes, and with the reengineering will take to out in 605 minutes; fitting stress that with the proposed posed, the owner of the workshop is save a time of 2025 minutes in all the processes developed in the same; What is beneficial because helps to the reduction of time, and to save both the resource materials, human and technological. As conclusion relevant of the work investigative is determined that them changes in them processes in the workshop will benefit to the same, achieving changes radical as the reduction of time, establishing responsible in each one of them processes, taking that meet with objectives, strategies, and goals that lead to the success of the workshop; before it is recommended to the Manager of the workshop, consider the reengineering proposed in those processes both strategic as operating.